TEACHING AND RESEARCHING ENGLISH FOR SPECIFIC PURPOSES, Elżbieta D. Lesiak-Bielawska (Krakow: Księgarnia Akademicka, 2018) - Escobar-Álvarez, Mª Ángeles (Miscelánea: A Journal of English and American Studies, 2021)
.